2013
DOI: 10.1016/j.jvb.2013.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Beyond conscientiousness: Career optimism and satisfaction with academic major

Abstract: The study focuses on psychological predictors of academic major satisfaction. According to the career construction theory (Savickas, 2005), vocational personality and career adaptability should generate career satisfaction. In this study, vocational personality was operationalized as Big Five conscientiousness, and career adaptability was operationalized as generalised self-efficacy and career optimism. A sample (N = 529) of university students completed an online survey. The resultant data were used to constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
2
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(93 citation statements)
references
References 23 publications
2
74
2
3
Order By: Relevance
“…En este sentido, un estudiante con un alto nivel de conciencia se compromete con sus estudios y está dispuesto a esforzarse más por alcanzar sus objetivos de la carrera, logrando así una mayor satisfacción académica (McIlveen, Beccaria y Burton, 2013).…”
Section: Inteligencia Emocional Engagement Académico Y Satisfacción unclassified
“…En este sentido, un estudiante con un alto nivel de conciencia se compromete con sus estudios y está dispuesto a esforzarse más por alcanzar sus objetivos de la carrera, logrando así una mayor satisfacción académica (McIlveen, Beccaria y Burton, 2013).…”
Section: Inteligencia Emocional Engagement Académico Y Satisfacción unclassified
“…In a very recent study, Tolentino et al (2014) highlighted that a solid body of research has shown the benefits of optimism on health-related adjustment (e.g., better quality of life and subjective well-being in Scheier & Carver, 1992; less psychological distress in Carver et al, 2005;Fitzgerald, Tennen, Affleck, & Pransky, 1993;Trunzo & Pinto, 2003) as well as on academic adjustment and satisfaction (Aspinwall & Taylor, 1992;McIlveen, Beccaria, & Burton, 2013). Furthermore, optimism has not only been found to predict adaptive career planning strategies (Creed et al, 2002), career optimistic individuals have also been reported to strive higher academically, report greater comfort with their educational and career-related plans, and engage in activities that enhance their career insight (Rottinghaus et al, 2005).…”
Section: Aim Of the Studymentioning
confidence: 99%
“…These findings corroborate previous findings relating poorer psychological functioning to poorer academic outcomes and better psychological functioning to better academic outcomes (Balanga et al, ; Close & Solberg, ; Zychinski & Polo, ). If an individual reports higher levels of life satisfaction, they may feel more optimistic or positive about their future possibilities (McIlveen, Beccaria, & Burton, ). This positive outlook on life may increase their desire to perform well in school, which would be related to academic motivation (McIlveen et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…If an individual reports higher levels of life satisfaction, they may feel more optimistic or positive about their future possibilities (McIlveen, Beccaria, & Burton, 2013). This positive outlook on life may increase their desire to perform well in school, which would be related to academic motivation (McIlveen et al, 2013).…”
Section: Discussionmentioning
confidence: 99%